Ecotoxicological evaluation of the application of landfill leachate on the germination of cabbage (Brassica oleracea var. capitata) - Franco, Heider Alves; Marques, Monica Regina da Costa; Martins, Gabrielle Marjory de Oliveira; Mussel, Yasmin Laureano; Thode Filho, Sérgio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
In sanitary landfills occurs the disposal of varied variety of residues that lead to the formation of leachate generated from the decomposition of urban solid wastes. Special attention should be given to leachate, as it may affect natural resources. The adoption of ecotoxicity tests may contribute to understand the relationship of pollutant with the environment in case of disposal or spillage. Thus, germination trials with cabbage (Brassica oleracea var. capitata) submitted to different dosages of landfill leachate (3.125%, 6.25%, 12.5%, 25%, 50% and 100%) were proposed in two substrates: paper filter and soil. The objective of this work was to evaluate the direct and indirect impact of the leachate on the germination of cabbage seeds, through the LC50 and the values of NOEC and LOEC. In both substrates it was not possible to determine the LC50 from the doses tested. In the paper test, the determination of LOEC, occurred with treatment 3.125%. For the soil test, the LOEC value is obtained with the 50% dose. The species presents a high potential for ecotoxicity bioassays to determine environmental impact, due to its sensitivity to variations in the environment.